Analisis dan Pengembangan Quality of Experience Website E-Commerce Menggunakan GTMetrix - Anhar Anhar; Muhammad Firdaus; Dimas Rama Aji Pangestu; Salpiana Salpiana; Jesica Amanda Putri (Department of Science and Technology Ibrahimy University, 2023)
The website is something that is familiar to hear at this time, where the world of technology, especially the internet, is developing rapidly. The development of the internet, in this case the website, is not only felt and used by business people, but also by the wider community, especially small businesses. The analytical method in this study uses the Automated usability testing tools approach which is used to test website performance. The performance is based on several general parameters, namely: performance, no of requests. Speed load time, page size. Parameter testing is measured using several tools: Pingdom, GTMetrix, Website Grader, Page Speed Insight, Site Analyzer and other Web Page Analyzer tools, performance is at a percentage of 30-38% and structure is at a percentage of 65-76%. The lowest access speed is 6.3 s and the highest is 29.5 s. Based on performance tests it is known that the system runs slowly and on average takes a long time, because image optimization means optimizing image size, so that image file sizes can be reduced. Measuring quality of experience (QoE) parameters on websites is very important to increase user satisfaction and reduce failure rate in the use of the website. Several QoE parameters that can be measured include load time, response speed, display quality, ease of use, user interface responsiveness, availability, reliability, and social interaction.